BIOCHEMICAL AND CHEMICAL OXYGEN DEMAND IN THE WATER OF LAKE BILIKOL (KAZAKHSTAN) (Journal of Geography and Environmental Management, 2026)
The results of chemical analyses of organic pollution indicators (COD(Cr), BOD₅) and dissolved oxygen in the water of Lake Bilikol over a long-term period (2007–2024 and summer 2025) are presented. The regime and dynamics of biological and chemical oxygen demand in Lake Bilikol depend on seasonal variations, the anthropogenic impacts of previous years, and the hydrological characteristics of the lake. Seasonal variability is determined by the additional input of organic matter into the lake with spring floodwaters, the frequency and intensity of water releases from the upstream Akkol Reservoir on the Asa River, as well as by ongoing internal processes occurring within the “water–bottom sediments” system.The average COD(Cr)/BOD₅ ratio was 4.24, indicating the possible presence of organic compounds that are resistant to biological degradation. No clear long-term pattern in COD(Cr) and BOD₅ values was identified across different seasons. However, a gradual decreasing trend has been observed since 2013. This trend is associated with increased sanitary water releases into Lake Bilikol containing lower concentrations of organic matter, as well as enhanced in-lake processes contributing to the self-purification of the water body. Nevertheless, the water quality of Lake Bilikol, based on COD(Cr) and BOD₅ indicators, does not comply with the regulatory standards established for water bodies used for fisheries purposes.
Keywords: organic matter; COD; BOD5; water pollution; dissolved oxygen